1989
DOI: 10.1002/esp.3290140504
|View full text |Cite
|
Sign up to set email alerts
|

Rates and patterns of bedrock denudation by coastal salt spray weathering: A seven‐year record

Abstract: Rapid surface lowering of bedrock is taking place in the supratidal zone by salt spray weathering. A seven-year run of data demonstrates a mean rate of lowering of 0-625 mm a-'. Considerable variation exists in annual point lowering values within measurement sites, although between-site variation is not significant. Aggregate year to year variations in surface lowering are not significant. Spatial variation in individual point values may be compensated by temporal variation over an 1 1-year period. There is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
1
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 22 publications
(16 reference statements)
4
73
1
1
Order By: Relevance
“…A similar study by Sperling and Cooke (1985) observed a second phase of rapid breakdown in some rocks after the slower phase observed in the earlier paper. Others, such as Goudie and Viles (1995) and Mottershead (1989), observed fairly constant weathering rates. The study by Mottershead (1989) is interesting because unlike the aforementioned laboratory studies it was a field-scale study of rock weathering.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…A similar study by Sperling and Cooke (1985) observed a second phase of rapid breakdown in some rocks after the slower phase observed in the earlier paper. Others, such as Goudie and Viles (1995) and Mottershead (1989), observed fairly constant weathering rates. The study by Mottershead (1989) is interesting because unlike the aforementioned laboratory studies it was a field-scale study of rock weathering.…”
Section: Introductionmentioning
confidence: 98%
“…Others, such as Goudie and Viles (1995) and Mottershead (1989), observed fairly constant weathering rates. The study by Mottershead (1989) is interesting because unlike the aforementioned laboratory studies it was a field-scale study of rock weathering.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Swelling events, ranging in some extreme cases up to several millimetres, can persist for a few months up to a couple of years. They have been attributed to salt crystallization, although wetting and drying is thought to play a less important role (Kirk, 1977;Mottershead, 1989;Stephenson and Kirk, 2001). Only a few TMEM stations on the sandstone and basalt platforms in the Bay of Fundy recorded mean rates of platform swelling (rock surface elevation between measurement intervals), but they were common on the argillite platform at Mont Louis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The gauge and probe sit on a low, triangular frame that, in use, is positioned on three metal bolts (a MEM station) permanently embedded in the rock surface (High and Hanna, 1970;Robinson, 1976). The instrument allows precise measurements to be made of slow rock downwearing (erosion in the vertical plane) and several workers have used it in the supra-and intertidal zones of rocky coasts (Kirk, 1977;Robinson, 1977;Gill and Lang, 1983;Mottershead, 1989;Stephenson and Kirk, 1998;Foote et al, 2001;Andrade et al, 2002). Unlike the MEM, which allows only three measurements to be made at each station, a traversing micro-erosion meter (TMEM) permits numerous measurements to be made within the triangular frame of the instrument (Trudgill et al, 1981;Stephenson, 1997).…”
Section: Fieldmentioning
confidence: 99%